Improvement of oxidation resistance of 9 mass% chromium steel for advanced-ultra supercritical power plant boilers by pre-oxidation treatment. (January 2017) - Abe, Fujio; Kutsumi, H.; Haruyama, H.; Okubo, H.
Highlights: Pre-oxidation treatment in argon gas containing 0.1 ppm to 1 volume % oxygen improves oxidation resistance of 9 mass% Cr steel in steam at 650 °C. A thin scale of Cr2 O3 -rich oxides is formed on the surface of 9Cr steel by the pre-oxidation treatment.The addition of Si enhances the formation of Cr2 O3 -rich oxide scale. Abstract: Effect of pre-oxidation treatment on oxidation resistance in steam at 650 °C has been investigated for 9 mass% chromium (Cr) steel for advanced ultra-supercritical power plants. The formation of thin scale of Cr2 O3 -rich oxides is achieved by pre-oxidation in argon gas containing 0.3 ppm oxygen, which significantly improves the oxidation resistance of the steel in steam at 650 °C for a long time exceeding 20, 000 h. Effects of pre-oxidation conditions, such as oxygen concentration in argon gas and pre-oxidation temperature and time, and of silicon concentration in the steel on the oxidation resistance in stream are systematically investigated.